AYAT-AYAT WAHDAT AL-WUJUd dalam Kitab Tanbi>h al-Ma>shi Karya ‘Abdurrauf al-Sinkili - Asep Nahrul Musadad (IAIN Ponorogo, 2015)
Abstract: One of the key moments in discussing the history of Indonesian Islam is a polemic related to the negotiation on the doctrine of wahdat al-wujud that occured in Aceh in 17th century between the followers of Hamzah al-Fansuri and Nuruddin al-Raniri. This article focuses on analyzing several Qur’anic verses used by ‘Abdurrauf as the confirmation of his argument. In the polemical context, Abdurrauf al-Sinkili appeared to be an actor of reconciliation between two opposite sides. He tried to respond to the disputed issues through his book called “Tanbi>h al-Mashi”. As an exponent of the so-called moderate sufism (mysticism), he built the argument concerning wahdat al-wujud based on the Quranic text. After making a thematic classification chronologically, his interpretation on these verses is analyzed by using Hussain al-Dhahaby’s theory of sufistic exegesis. In conclusion, it shows that ‘Abdurrauf’s commentary is “sufi-nazari type”, featured by his exegeses pattern. This, of course, represents his attitude as a reconciler who then needs to seek confirmation to the Qur’anic verses in evaluating wahdat al-wujud doctrine, through which such a polemical issues occurred at that time. الملخص: إن من المرحلة الأساسية التي مرّ بها تاريخ الإسلام في اندونيسيا الجدل و النزاع حول عقيدة وحدة الوجود فى أتشيه (Aceh) حول قرن السابع عشر بين أتباع حمزة الفنسوري و نور الدين الرانيري. ففي ذلك الخطاب النزاعي جاء عبد الرؤوف السنكيلي مصلحا بين الجانبين المعاكسين. وعلى مقتضى الظروف، كتب كتاب